2012
DOI: 10.5858/arpa.2012-0263-ra
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Lung Cancer in Small Biopsies and Cytology: Implications of the 2011 International Association for the Study of Lung Cancer/American Thoracic Society/European Respiratory Society Classification

Abstract: The new International Association for the Study of Lung Cancer/American Thoracic Society/European Respiratory Society lung adenocarcinoma classification provides, for the first time, standardized terminology for lung cancer diagnosis in small biopsies and cytology; this was not primarily addressed by previous World Health Organization classifications. Until recently there have been no therapeutic implications to further classification of NSCLC, so little attention has been given to the distinction of adenocarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
365
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 373 publications
(375 citation statements)
references
References 93 publications
5
365
1
4
Order By: Relevance
“…With the advances in targeted therapeutics, physical tissue must be collected for molecular testing to determine whether tumors harbor mutations that would benefit from targeted therapy. This requirement precludes replacement of tissue biopsy with OCT and other in vivo optical biopsy techniques because, to date, they are unable to provide this essential mutational information (5,6).…”
Section: Original Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…With the advances in targeted therapeutics, physical tissue must be collected for molecular testing to determine whether tumors harbor mutations that would benefit from targeted therapy. This requirement precludes replacement of tissue biopsy with OCT and other in vivo optical biopsy techniques because, to date, they are unable to provide this essential mutational information (5,6).…”
Section: Original Researchmentioning
confidence: 99%
“…New therapeutic discoveries have driven a dramatic effort to subtype poorly differentiated carcinomas as either SCCs or adenocarcinomas even on small tissue specimens (2, 4-6), but one study showed that only 32% of poorly differentiated carcinomas could be accurately subtyped on FNA by morphology alone (45). Immunohistochemical studies can be performed to aid subtyping, but these studies do not always provide a clear answer and there is also significant concern regarding tissue preservation for molecular testing work-ups (2,(4)(5)(6). In this study, the readers were able to correctly diagnose the carcinoma subtype (SCC or adenocarcinoma) with OCT in 71% of poorly differentiated carcinoma cases that could not be subtyped by morphological features on histology.…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of patients with pulmonary carcinoma have non-resectable advanced disease [11,12]; as a result, only minimally invasive non-surgical tissue-sampling is often performed. However, diagnostic demands are increasing due to the importance of correctly characterising each malignancy.…”
Section: Diagnostic Steps In Nsclcmentioning
confidence: 99%
“…A limited number of IHC stains can be utilised on NSCLC-NOS cases to determine whether such cases represent adenocarcinoma or squamous cell carcinoma, bearing in mind that IHC cannot predict the subtype in approximately one fifth of NSCLC-NOS cases [16] (Table 1). Minimum recommendations for IHC include the use of antibodies for TTF-1 (for adenocarcinoma) and p63 or p40 (for squamous cell carcinoma) [12,17]. It is important to interpret the IHC tests according to validated levels of staining [16]; for example, squamous predictive markers generally require strong, diffuse staining for accurate diagnosis.…”
Section: Diagnostic Steps In Nsclcmentioning
confidence: 99%